Rancang Bangun Fire Alarm dan Smoke Detector Berbasis Programmable Logic Controller (PLC) Tyfe SR3B261BD - Hafis Darmawan; Venny Yusiana; Herberth Siregar (Journal of Electrical Power Control and Automation (JEPCA), 2022)
Programmable logic controller (PLC) can be design for various purposes, one of which is to design a fire extinguishing system, by assembling several components of PLC, solenoid, spingkle, power supply, adaptor,smoke detector, heat detector, pilot lamp, push button,relay, selector switch, Design the program setting to detect smoke and high temperetures that occur in the event of a fire. If the smoke detector detect smoke and high temperatures, the sensor will give a signal to the plc to turn on and activate all working components and extinguish the fire. . In the future, the use of this tool can be installed in lecture rooms in Unbari, especially the Faculty of Engineering room and developed for the use of Human Interface which is directly connected to firefighters.